Nova metodologia de obtenção de nanopartículas de vidro bioativo, poliuretanas biodegradáveis e seus compósitos para aplicações biomédicas - Agda Aline Rocha de Oliveira (2011)
Since developed by Hench as a promising bone repairing material with high bioactivity and biocompatibility, bioactive glass has attracted extensive studies. Various investigations were directed to obtain solgel derived bioactive glasses as bulk, powder or porous scaffolds. Nanotechnology gives a new strategy to develop bioactive glasses, since nanoscaled biomaterials exhibit an enhanced biocompatibility and bioactivity.The development of polymer/bioactive glass has been recognized as a strategy to improve the mechanical behavior of bioactive glass-based materials. Several studies have reported systems based on bioactive glass nanoparticles/ biopolymer composites. In this work it was developed a composite system based on bioactive glass nanoparticles(BGNP), obtained by a modified Stober method. The size, composition, shape and dispersion capability of the obtained particles were studied by several techiques. The BGNP obtained have spherical shape and average size of 20 nm, as prepared, and 90 nm, after heat treatment. Nanoparticles presented significant increase in cell viability when compared to microparticles. They present good dispensability on polar solvents and could offer superior performance for developing tissue scaffolds.The polymeric phase is extremely important to design the final properties of the composites. The highly variable synthesis chemistry of segmented polyurethanes (PUs) may be exploited to generate polymers having properties ranging from very soft elastomers to very rigidplastics. In addition to the physical properties, a great care has to be taken in the choice of the building blocks. Their degradation products have to be biocompatible, non-toxic and metabolized or eliminated by the living organism.Another aim of this work is the developed of a new chemical route to obtain aqueous dispersive biodegradable polyurethane. This chemical procedure was well succeeded in producingPU dispersions with solid content about 20%. Films were obtained by casting the dispersions in molds and allowing them to dry at room temperature. Porous scaffold were produced by dilution and freeze drying of the dispersion obtained. The films had 250% of deformation and the foams presented interconnected macroporous. The study of degradations products showed a moderated toxic effect and more studies have to be done to evaluated the release of these products at concentrations closer to the in vivo conditions.The ultimate goal was associated the newly developed components (BGNP and PU aqueous dispersions) to produce membranes and scaffolds, intending toassociate biocompatibility, mechanical and physical properties in a material designed for tissue engineering applications. The composites were obtained by the dispersion of BGNP in a polivynyl alcohol solution and then, the mixture was added to PU dispersion, with BGNP composition of 0, 10 and 25%. The films had 350% of deformation and the foams presented mechanical properties adequaded for tissue engineering applications. The materials presented good cell viability andhydroxyapatite layer formation.